Layout Analysis of Goods Storage: Case Study Spare Part Warehouse Z Company - Edo Wijaya (Jurnal Rekayasa Sistem Industri, 2022)
This research is a case study to solve the problems that occur at PT. Z, which is engaged in palm oil processing. The case raised is the spare parts warehouse of PT. Z, where the problem that has occurred so far is the policy of random storage in the spare parts warehouse. This results in irregularities that complicate the process of receiving, storing, searching and releasing spare parts, which is indicated by the high total travel distance in the warehouse. Thus, the purpose of this study is to minimize the total travel distance in the spare parts warehouse by using a dedicated storage policy which is based on an analysis of the product storage layout (spare parts). Based on the results of data processing using a dedicated storage policy, the initial trip distance is 4257.25 meters and the proposed trip distance is 4002,5 meters. From these conditions, it can be concluded that using a dedicated storage policy can reduce the total travel distance in the spare parts warehouse by 254,75 meters or around 5,9%.